Case studies of near misses in clinical anesthesia - Brock-Utne, J. G.; SpringerLink (Online service). (New York, NY Springer Science+Business Media, LLC, 2011)
All anesthesiologists eventually face the fear of a "near miss," when a patient's life has been put at risk. Learning from the experience is crucial to professionalism and the ongoing development of expertise. Drawing on forty-plus years of practice in major metropolitan hospitals in the United States, Norway, and South Africa, John Brock-Utne, MD presents 80 carefully selected cases that provide the basis for lessons and tips to prevent potential disaster. The cases emphasize problem-centered learning and span a broad range of topics?from an outbreak of operating room infection (could it be the anesthesia equipment?), complications of fiberoptic intubations, and problems with epidural drug pumps, to performing an urgent tracheostomy for the first time, working with an aggressive surgeon, and what to do when a patient falls off the operating table during surgery. 80 true-story clinical near misses never before published. Ideal for problem-centered learning. Recommendations, references, and discussions accompany most cases. Rich basis for teaching discussions both in or out of the operating room. Settings include sophisticated as well as rudimentary anesthetic environments. Complements the author's other case book, Clinical Anesthesia: Near Misses and Lessons Learned (Springer, 2008)
Case 1. A patient with a mediastinal mass -- Case 2. Stick out your tongue -- Case 3. An epidural blood patch. What went wrong? -- Case 4. A lack of communication leads to a bad outcome -- Case 5. Hyperkalemia during Coronary Artery Bypass Graft -- Case 6. A adjuvant to the cuff leak test -- Case 7. Acinetobacter baumannii outbreak in an ICU. Can our equipment be at fault? -- Case 8. A complication with the use of the intubating Fiberscope -- Case 9. Interscalene block in concern in cardiac patients -- Case 10. Epidural analgesia for labor. Watch out -- Case 11. Past history of esophagectomy. Any concern? -- Case 12. A case of Myasthenia Gravis -- Case 13. Where are my teeth? -- Case 14. An unusual Capnograph tracing -- Case 15. A VP shunt -- Case 16. Shoulder surgery. Watch out -- Case 17. An ambulatory surgical patient with no escort -- Case 18. A complication during laprascopy -- Case 19. A patient with Amyotrophic lateral sclerosis -- Case 20. Repair of a thoracic duct -- Case 21. Occuled reinforced (armored) endotracheal tube -- Case 22. A difficult nasogastic tube insertion -- Case 23. Antiphospholipid antibody syndrome. Any concern for general anesthesia? -- Case 24. An airway surprise -- Case 25. Difficulty with breathing in the postoperative period -- Case 26. Severe systemic local anesthetic toxicity -- Case 27. A motorcycle accident with neck injury -- Case 28. Thoracic incisional injury -- Case 29. Bronchospasm. An unusual cause -- Case 30. Post bariatric surgery. Any concerns? -- Case 31. Valuable information from an implanted pacemaker -- Case 32. Allen?s test in an anesthetized patient. Is it possible? -- Case 33. A loss of the only oxygen supply you have during an anesthetic -- Case 34. An aggressive surgeon -- Case 35. A pharyngeal mass -- Case 36. Retained laps -- Case 37. A ?Code Blue? -- Case 38. A complication of Transesophageal echocardiography (TEE) -- Case 39. LMA in elective orthopedic surgery -- Case 40. What would you do? -- Case 41. Preeclampsia -- Case 42. A failed ?test dose? -- Case 43. A simple cystoscopy with biopsy -- Case 44. An orthopedic trauma -- Case 45. Blood in the endotracheal tube -- Case 46. A longstanding tracheostomy -- Case 47. An airway problem during MAC -- Case 48. Is the patient extubated? -- Case 49. A leaking anesthesia machine -- Case 50. A most important lesson -- Case 51. Transsphenoidal resection of a pituitary tumor -- Case 52. Spinal reconstruction and fusion in a chronic pain patient -- Case 53. A repeat back operation in a patient who has had postoperative visual loss in the past -- Case 54. Respiratory arrest in the recovery room -- Case 55. Bispectral Index. What does it mean? -- Case 56. Neonatal laprascopic surgery -- Case 57. Total IV anesthesia -- Case 58. An ICU Patient -- Case 59. A new onset of arterial fibrillation in the recovery room -- Case 60. A rapid increase in core body temperature -- Case 61. Prolonged surgery -- Case 62. Persistent intraoperative hiccups. What to do? -- Case 63. Internal jugular cannulation -- Case 64. Endobronchial foreign body -- Case 65. A cyst in Fourth ventricle -- Case 66. Generalized convulsions after regional anesthesia -- Case 67. Cardiac arrest in a prone patient -- Case 68. A short patient with a high BMI -- Case 69. Bleeding after oral surgery -- Case 70. Selecting the right size double lumen tube -- Case 71. A low normal preoperative blood glucose level -- Case 72. Things to remember when you change a Cordis Catheter to a triple lumen -- Case 73. An intraoperative malfunctioning vaporizer -- Case 74. An abnormal EKG first discovered in the operating room -- Case 75. A cardiac arrest in ICU -- Case 76. A severe case of metabolic acidosis -- Case 77. Bunionectomy under both general and regional anesthesia -- Case 78. Now what would you do? -- Case 79. A strange case -- Case 80. A chronic pain patient.
Electronic reproduction.
Keywords: Anesthesiology; Anesthesia; Anesthesia -- Adverse effects -- Case Reports; Electronic books